Absolute measurement of species differences in sodium taurocholate cotransporting polypeptide (NTCP/Ntcp) and its modulation in cultured hepatocytes. Issue 9 (8th May 2013) - Qiu, Xi; Bi, Yi‐An; Balogh, Larissa M.; Lai, Yurong; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract Species differences among membrane transporters can be remarkable and difficult to properly assess by conventional methods. Herein, we employed the first use of stable isotope labeling in mammals or stable isotope‐labeled peptides combined with mass spectrometry to identify species differences in sodium taurocholate cotransporting polypeptide (NTCP/Ntcp) protein expression in liver tissue and to characterize the modulation of protein expression in sandwich‐cultured human (SCHH) and rat hepatocytes (SCRH). The lower limit of quantification was established to be 5 fmol on column with a standard curve that was linear up to 2000 fmol. The accuracy and precision were evaluated with three quality control samples and known amounts of synthetic proteotypic peptides that were spiked into the membrane protein extracts. The overall relative error and coefficient of variation were less than 10%. The expression of Ntcp in mouse and rat was significant higher than that in human (five‐fold) and monkey (two‐fold) and ranked as mouse > rat >> monkey > human. In the cultured hepatocytes, although significant downregulation of Ntcp expression in SCRH at day 5 after the culture was detected, NTCP expression in SCHH was comparable to the suspension hepatocytes. The results suggested that NTCP/Ntcp modulation in cultured hepatocytes is species specific. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3252–3263, 2013